Molecular gas towards G18.8+1.8 - Vasquez, Javier (2012)
Aims. This work aims at investigating the characteristics of the molecular gas associated with the nebula G18.8+1.8, which is linked to the Wolf-Rayet star HD 168206 (WR 113), and its relation to other components of its local interstellar medium. Methods. We carried out molecular observations of the 12CO(J = 1−0) and (J = 2−1) lines with an angular resolution of 44′′ and 22′′ using the SEST telescope. Complementary NANTEN data of the 12CO(1−0) line were also used. The dust emission was analyzed using Spitzer-IRAC images at 8.0 μm, and WISE data at 3.4 μm, 4.6 μm, and 12.0 μm. Results. The SEST data allowed us to identify a molecular component (Cloud 3) that has velocities in the interval from ~+30 to +36 km s-1 and is most probably linked to the nebula. Morphological and kinematical properties suggest that Cloud 3 consists of a wind-blown molecular half-shell, which expands around WR 113. The ratio R2−1/1−0 and excitation temperatures indicate that the molecular gas is being irradiated by strong UV radiation. The location of the inner optical ring in the outer edge of Cloud 3 suggests that the stars SerOB2-1, -2, -3, -63, and -64 are responsables for the ionization of Cloud 3 and the inner ring nebula. A comparison between the spatial distribution of the molecular gas and the PAH emission at 8 μm indicates the existence of a photodissociation region between the ionized and the molecular gas. A search for candidate young stellar objects (YSOs) in the region around G18.8+1.8 based on available 2MASS, MSX, IRAS, and Spitzer-IRAC catalogs resulted in the detection of about sixty sources, some of them projected onto Cloud 3. Two small spots of clustered candidate YSOs are projected near the outer border of Cloud 3, although a triggered stellar formation scenario is doubtful.